Improving the Students’ Reading Skill using Multiple Intelligences Approach - IKA PUSPITARINI (Fakultas Sastra Universitas Gresik, 2017)
This paper is aimed to discuss the advantages gained by both the teachers and learners in reading class using multiple intelligences approach. In many second or foreign language learning teaching situations, reading has received special focus, especially on how students develop their reading comprehension skill. The theory of Multiple Intelligences (MI) allows teachers have to detect studentsÃ¢â‚¬â„¢ strengths and weaknesses in the classroom. Therefore, teachers are encouraged to begin to think of lesson planning in terms of meeting the needs for improving studentsÃ¢â‚¬â„¢ reading skill by maximizing their dominant intelligences. Key words: teaching reading, multiple intelligences, maximizingÃ‚Â